A ‘Bermuda Triangle’ Effect Shaping Reef Fish Connectivity Across the Western Atlantic - Melissa Scheel‐Dalmau; Jose Julian Tavera; Kenyon C. Lindeman; David Snyder; Claudio Oliveira; Struan R. Smith; Carmen del Rocío Pedraza‐Marrón; Arturo Acero P; Ricardo Betancur‐R (Molecular Ecology, 2026)
Understanding the spatial scale and structure of marine connectivity is essential for uncovering how ocean currents shape gene flow, population structure and larval transport in reef organisms. We examined range‐wide patterns of gene flow and population structure in the tomtate ( Haemulon aurolineatum ), an abundant reef fish with a broad distribution from southern Brazil to Bermuda in the western Atlantic. We used genome‐wide SNPs, mitochondrial DNA sequences and a re‐evaluation of morphological variation to assess connectivity, demographic history and lineage boundaries across 22 locations spanning all major biogeographic provinces within the species' range. Population structure and phylogenetic analyses identified three main genetic groups: (1) the Caribbean and Southwestern Atlantic (CSA), (2) the Gulf of Mexico (GOM) and (3) Bermuda (BDA), with further substructure within CSA. Demographic modelling and migration analyses supported early divergence followed by sustained but asymmetric gene flow, particularly into BDA, which acts as a long‐term demographic sink, likely maintained by episodic larval input from CSA and GOM. This pattern aligns with previous findings from biophysical models and larval transport studies. Recognized marine barriers such as the Eastern and Western Caribbean breaks contributed to population differentiation, while coastal corridors along Brazil and the Guianas facilitated northward gene flow. Coalescent‐based species delimitation supported three species‐level lineages, but we interpret these as subspecies: morphologically and genomically distinct, yet not fully reproductively isolated. Taken together, these results demonstrate how asymmetric dispersal and oceanographic isolation can structure genetic diversity in marine organisms by creating peripheral demographic sinks like Bermuda, where limited and unidirectional connectivity promotes long‐term differentiation—a pattern we describe as the ‘Bermuda Triangle effect.’

Diet Outweighs Vertical Transmission in Shaping Dung Beetle Larval Gut Microbiomes - Michelle J. Herrera; Avi Khanna; Joshua A. Jones; Ricardo Betancur‐R.; Patrick T. Rohner (Molecular Ecology, 2026)
The microbiome is central to host development and adaptation, yet the balance between vertical and environmental acquisition, and how hosts shape surrounding microbial communities, remains poorly understood. Dung beetles rely on microbial symbionts to extract nutrients from vertebrate dung, with part of their microbiome vertically inherited via a maternal faecal pellet. However, the relative importance of vertical versus horizontal transmission is unclear. We examined this in the gazelle dung beetle ( Digitonthophagus gazella ), rearing larvae on brood balls made of dung from grass‐(high‐quality), hay‐(low‐quality) or silage‐fed (a novel fermentable energy‐rich diet) cattle, with or without maternal microbes. We integrated measures of gut morphology with 16S rRNA amplicon sequencing to assess host development and the gut microbiome. Diet significantly influenced overall size, hindgut area, and microbiome composition. Silage‐dung fed larvae had more even and taxonomically rich microbiomes, with higher microbial diversity in individuals reared with maternal microbes. Diet explained ~26% of the variation in microbial composition, while the vertical transmission of microbes only explained 3%. Vertical transmission only slightly increases microbial species richness and relative hindgut area but did not influence overall microbial diversity. The larval brood ball contributed 40%–50% of the hindgut microbiome, while maternal microbes contributed

Congruence between microsatellite loci, SNPs, and COI gene reveals a phylogeographic break in the southern Caribbean Sea: The case of West Indian top shell Cittarium pica (Gastropoda: Tegulidae) - Juan Carlos Narváez Barandica; Julian F. Quintero-Galvis; Ana Caruso Vargas; Germán Blanco Cervantes; Juan Carlos Aguirre Pabón; Lyda Castro García; Ricardo Betancur-R.; Arturo Acero P. (Fisheries Research, 2024)

The marine catfishes of the genus Bagre (Siluriformes; Ariidae) from the Western Atlantic - Alexandre P. Marceniuk; Claudio Oliveira; João Bráullio L. Sales; Ricardo Betancur-R (Marine Biodiversity, 2022)

Biogeography, habitat transitions and hybridization in a radiation of South American silverside fishes revealed by mitochondrial and genomic RAD data - Lily C. Hughes; Yamila P. Cardoso; Julie A. Sommer; Roberto Cifuentes; Mariela Cuello; Gustavo M. Somoza; Mariano González‐Castro; Luiz R. Malabarba; Victor Cussac; Evelyn M. Habit; Ricardo Betancur‐R.; Guillermo Ortí (Molecular Ecology, 2020)
Rivers and lake systems in the southern cone of South America have been widely influenced by historical glaciations, carrying important implications for the evolution of aquatic organisms, including prompting transitions between marine and freshwater habitats and by triggering hybridization among incipient species via waterway connectivity and stream capture events. Silverside fishes ( Odontesthes ) in the region comprise a radiation of 19 marine and freshwater species that have been hypothesized on the basis of morphological or mitochondrial DNA data to have either transitioned repeatedly into continental waters from the sea or colonized marine habitats following freshwater diversification. New double digest restriction‐site associated DNA data presented here provide a robust framework to investigate the biogeographical history of and habitat transitions in Odontesthes . We show that Odontesthes silversides originally diversified in the Pacific but independently colonized the Atlantic three times, producing three independent marine‐to‐freshwater transitions. Our results also indicate recent introgression of marine mitochondrial haplotypes into two freshwater clades, with more recurring instances of hybridization among Atlantic‐ versus Pacific‐slope species. In Pacific freshwater drainages, hybridization with a marine species appears to be geographically isolated and may be related to glaciation events. Substantial structural differences of estuarine gradients between these two geographical areas may have influenced the frequency, intensity and evolutionary effects of hybridization events.

Comparative phylogeography of trans‐Andean freshwater fishes based on genome‐wide nuclear and mitochondrial markers - Melissa Rincon‐Sandoval; Ricardo Betancur‐R; Javier A. Maldonado‐Ocampo (Molecular Ecology, 2019)
The Neotropical region represents one of the greatest biodiversity hot spots on earth. Despite its unparalleled biodiversity, regional comparative phylogeographic studies are still scarce, with most focusing on model clades (e.g. birds) and typically examining a handful of loci. Here, we apply a genome‐wide comparative phylogeographic approach to test hypotheses of codiversification of freshwater fishes in the trans‐Andean region. Using target capture methods, we examined exon data for over 1,000 loci combined with complete mitochondrial genomes to study the phylogeographic history of five primary fish species (>150 individuals) collected from eight major river basins in Northwestern South America and Lower Central America. To assess their patterns of genetic structure, we inferred genealogical concordance taking into account all major aspects of phylogeography (within loci, across multiple genes, across species and among biogeographic provinces). Based on phylogeographic concordance factors, we tested four a priori biogeographic hypotheses, finding support for three of them and uncovering a novel, unexpected pattern of codiversification. The four emerging inter‐riverine patterns are as follows: (a) Tuira + Atrato, (b) Ranchería + Catatumbo, (c) Magdalena system and (d) Sinú + Atrato. These patterns are interpreted as shared responses to the complex uplifting and orogenic processes that modified or sundered watersheds, allowing codiversification and speciation over geological time. We also find evidence of cryptic speciation in one of the species examined and instances of mitochondrial introgression in others. These results help further our knowledge of the historical geographic factors shaping the outstanding biodiversity of the Neotropics.

Fossil‐based comparative analyses reveal ancient marine ancestry erased by extinction in ray‐finned fishes - Ricardo Betancur‐R; Guillermo Ortí; Robert Alexander Pyron (Ecology Letters, 2015)
The marine‐freshwater boundary is a major biodiversity gradient and few groups have colonised both systems successfully. Fishes have transitioned between habitats repeatedly, diversifying in rivers, lakes and oceans over evolutionary time. However, their history of habitat colonisation and diversification is unclear based on available fossil and phylogenetic data. We estimate ancestral habitats and diversification and transition rates using a large‐scale phylogeny of extant fish taxa and one containing a massive number of extinct species. Extant‐only phylogenetic analyses indicate freshwater ancestry, but inclusion of fossils reveal strong evidence of marine ancestry in lineages now restricted to freshwaters. Diversification and colonisation dynamics vary asymmetrically between habitats, as marine lineages colonise and flourish in rivers more frequently than the reverse. Our study highlights the importance of including fossils in comparative analyses, showing that freshwaters have played a role as refuges for ancient fish lineages, a signal erased by extinction in extant‐only phylogenies.

Apparent signal of competition limiting diversification after ecological transitions from marine to freshwater habitats - Ricardo Betancur‐R.; Guillermo Ortí; Ariel M. Stein; Alexandre P. Marceniuk; R. Alexander Pyron (Ecology Letters, 2012)
Adaptive radiations are typically triggered when a lineage encounters a significant range of open niche space (ecological opportunity), stemming from colonisation of new areas, extinction of competitors or key innovations. The most well‐known of these is the colonisation of new areas, through either dispersal into new regions or the invasion of novel ecological regimes. One aspect of ecological opportunity that has rarely been studied, however, is the extent to which pre‐existent competitors act to limit diversification in newly colonised adaptive zones. Herein, we show that in multiple geographically independent invasions of freshwaters by marine Sea Catfishes (Ariidae), rates of both morphological disparification and lineage diversification are inversely related to the presence and diversity of other freshwater fish lineages. Only in one region (Australia‐New Guinea) with an otherwise depauperate freshwater fauna, has an ariid invasion gained any substantial traction. This is true at both regional and community scales, suggesting that competitive constraints may be an important factor regulating adaptive radiation.